Evaluation of the Effectiveness of Community Involvement Program of Education and Nursing Students - Tomas, Maria Anita (JPAIR Institutional Research, 2022)
The college department conducted this research study to evaluate the effectiveness of the community involvement program (CIP) in terms of health, literacy, and numeracy services rendered by nursing and education students in Matangtubig from 2015-2020.The study utilized participatory research. It involves stakeholders in Barangay Matangtubig in community projects, evaluating, collecting, and analyzing data. The information taken will be utilized to adjust and improve the project. The study explored the experience of Barangay Matangtubig residents in terms of health care and tutorial services rendered by the college students at a private school, specifically the Bachelor of Science in Nursing (BSN) and Education. It investigated the participants’ experience with the health care services delivered regarding maternal and child health care, health education, nutrition, environmental sanitation of the community, and education regarding reading, writing, and numeracy services. The results of the study provided baseline information for policymakers in designing programs, setting standards, and taking necessary actions. The study revealed that people in the community must assume personal responsibility to become self-reliant. The presence of the nursing and education students was meant only to facilitate and help the residents.